The The Effect of SABELS and GRPQ on The Students’ Reading Comprehension at SMA Swasta RK Bintang Timur Pematangsiantar - Pardede , Hilman (Pascasarjana Universitas HKBP Nommensen, 2021)
The aim of this research is to find out the effect of Scientific Approach-Based on English Learning Strategy (SABELS) and Guided Reading Peer Questioning Strategy (GRPQ) on students’ reading comprehension at grade X of SMA Swasta RK Bintang Timur Pematang Siantar. The researchers used quantitative method. The mean of GRPQ strategy is 77.50, Standard Deviation is 7.75, and significance value is .002 and number of students is 36. The mean in SABELS strategy is 80.00 and standard deviation is 9.25, and significance value is 0.38 and number of students is 36. The class who got conventional strategy, it has mean 75.00, standard deviation is 7.50, and significance value is .000 and number of students is 37. Using t-test in analyzing data, is found that t-value (2,36) is higher that t-table (1,667) at level of significant 5 %. This means using SABELS is effective to develop students’ ability in reading comprehension. According to the research findings, it is concluded that SABELS is more significant than GRPQ Strategy in teaching reading comprehension at tenth grade students at SMA Swasta RK Bintang Timur Pematangsiantar.